Endoscopic ultrasound-guided fine-needle aspiration with on-site cytopathology versus core biopsy: a comparison of both techniques performed at the same endoscopic session - Lin, Michael; Hair, Clark D.; Green, Linda K.; Vela, Stacie A.; Patel, Kalpesh K.; Qureshi, Waqar A.; Shaib, Yasser H. (Endoscopy International Open, 2014)
Background: Endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) with bedside cytopathology is the gold standard for assessment of pancreatic, subepithelial, and other lesions in close proximity to the gastrointestinal tract, but it is time-consuming, has certain diagnostic limitations, and bedside cytopathology is not widely available. Aims: The goal of this study is to compare the diagnostic yield of EUS-guided FNA with on-site cytopathology and EUS-guided core biopsy. Methods: Twenty-six patients with gastrointestinal mass lesions requiring biopsy at a tertiary medical center were included in this retrospective analysis of a prospective cohort. Two core biopsies were taken using a 22 gauge needle followed by FNA guided by a bedside cytopathologist at the same endoscopic session. The diagnostic yield and test characteristics of EUS core biopsy and EUS FNA with bedside cytopathology were examined.Results: The mean number of passes was 3.2 for FNA, and the mean procedure time was 39.4 minutes. The final diagnosis was malignant in 92.3 %. Sensitivity and specificity were 83 % and 100 %, respectively, for FNA, and 91.7 % and 100 %, respectively, for core biopsy. Diagnostic accuracy was 92.3 % for FNA and 84.6 % for core biopsy. The two approaches were in agreement in 88.4 % with a kappa statistic of 0.66 (95 % confidence interval 0.33 – 0.99). Conclusions: An approach using two passes with a core biopsy needle is comparable to the current gold standard of FNA with bedside cytopathology. The performance of two core biopsies is time-efficient and could represent a good alternative to FNA with bedside cytopathology.